The role of financial methods and instruments in economic growth - Momotyuk, L. E. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2017)
Most common approaches to constructing the system of financial methods and their structuring are summed up for effective implementation of the financial policy at country level. Implementation of financial policy requires clear approaches to elaboration, systematization and improvement of financial methods. The financial system is incapable of providing all the necessary solutions on financial support for the sustained rates of economic growth. Financial methods and corresponding instruments, once properly constructed and systematized, are not only central to economic growth, but allow for timely response on any change in the global financial system and for taking adequate decisions. Financial methods can be defined as purposeful and concrete practical actions in the financial sphere, combinations of various financial instruments, methods and techniques, their links and coordination in order to achieve macroeconomic and macro financial objectives. Financial methods are implemented by use of various financial instruments. Each financial instrument is in a way autonomous from the other financial instruments. At the phase of economic growth, monetary instruments need to be coordinated with and linked to fiscal instruments, which are the ones that reduce inflation expectations, influence prices, encourage labor productivity growth etc.